Physiological potential of pigeon pea seeds under packaging, drying and storage conditions (Research, Society and Development, 2020)
The objective of this study was to evaluate the physiological quality of pigeonpea seeds submitted to different drying conditions during storage in different packages. The experiment was installed in a completely randomized design, in a 3x4x5 factorial scheme (three drying conditions: oven drying, drying in an experimental dryer and half shade drying; four types of packaging: Pet bottle, Tetrapak box, Nylon bag and 5 L Pet Gallon with candle and five storage periods: 0, 30, 60, 90 and 120 days). Seed quality was evaluated by the germination pattern, moisture content, electrical conductivity, emergence and accelerated aging. The type of packaging influences the quality of pigeonpea seeds during storage. The packaging of pigeon pea seeds in Pet bottle allows greater conservation of germination and vigor during the 120 days of storage. The condition of drying in half shade guarantees greater physiological quality of pigeon pea seeds during 120 days of storage.